Antara Sastra dan Rasa Kebangsaan: Menuju Situasi Sadar Budaya pada Unsur Nilai Kearifan Lokal sebagai Suatu Mekanisme Rasa Aman di Tanah Papua - Habel Samakori (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Local wisdom developments that relevant and contextual have necessary meaning for progress a nation, particulaly if it is seen from culture tobustness side and its region identity. Culture of society consist of all something which shall be known or trusted by someone to be able to behavior in admissible by member of society itself. Culture constitutes organization of man's think (mind), model were had by man to accept, connect, and interpreted various phenomenon kind significant. When we develop the concept to empirical domain, we agreed that culture also concern feel accepts elements from outside, regard, refuse, relate, and gives good or bad assessment.